Synergistic effect of pH-shifting and Maillard reaction on the structure and function of carp by-product protein isolate - Yanjun Liu; Yanan Mo; Yixiao Shen; Ling Liu (Food Hydrocolloids, 2026)

Taurine attenuates heat stress-induced intestinal permeability by inhibiting endoplasmic reticulum stress and modulating gut microbiota - Haoran Jiang; Fan Mo; Zhuobin Pan; Chong Wang; Yanjun Cui (Journal of Thermal Biology, 2026)

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Towards new bioactive fluorine-containing 1,3,4-oxadiazole-amide derivatives: synthesis, antibacterial activity, molecular docking and molecular dynamics simulation study - Fei Xiong; Yanjun Zhang; Jinlong Jiao; Yiren Zhu; Tianlu Mo; Yeji Li (Molecular Diversity, 2025)

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

Offshore, Unmanned Auto-Leveling Sea-Surface Drifting Platform with Compact Size - Zonglai Mo; Kexiang Li; Kefeng Xie; Jun Li; Yanjun Li (Journal of Marine Science and Engineering, 2023)
This paper proposes an offshore, unmanned auto-leveling sea-surface drifting platform, with a compact size of 0.7 m in diameter, used for obtaining air-sea interface environmental parameters. The platform was designed based on the parallel mechanism with limited degrees of freedom. The mechanical structure, control system hardware, and software of the principal prototype are introduced. A ground-based device was developed to simulate wave disturbance, based on which the static and dynamic simulation experiments were carried out. Experimental results show that the auto-leveling system can achieve real-time leveling against the angle deviation induced by waves, with a leveling accuracy of 0.2° in a simulated wave with an angle of 12°, which meets the requirements of observation equipment.

A Small Floating Platform Designed for Unmanned Defense System - Zonglai Mo; Kefeng Xie; Fengcheng Zhao; Jun Li; Yanjun Li (Journal of Marine Science and Engineering, 2023)
A small floating platform designed for an unmanned short-range defense system is proposed. The structures of the proposed floating platform and weapon system are detailed and described. The floating platform is investigated via virtual prototype technology in the aspects of the platform motion under sea waves of up to Beaufort wind and Douglas sea (wind-sea) scale 5. The motion equations of the floating platform are established according to the ship motion theory, and the movement of the floating platform under different wind-sea scales are simulated and analysed via multi-body fluid dynamics analysis software. To decide the proper size of the platform, the dynamic response of the floating platforms with different sizes is analysed and evaluated under various sea conditions based on multi-body dynamics. A scaled model experiment was conducted and compared with simulation results to verify the theoretical model. A verification experiment was also conducted in a water tank for the performance of the platform via simulated wave disturbance. Results show that the designed floating platform could provide a stable platform in the horizontal direction under a wind-sea scale 3 environment for the defense weapon system, which well meets the design requirement.